Who is leading the digital transformation? Understanding the adoption of digital technologies in Germany - Clemens Ohlert; Oliver Giering; Stefan Kirchner (New Technology, Work and Employment, 2022)
Debates on digitalisation in Germany often refer to 'Industrie 4.0' describing a seamless and technology-driven process spearheaded by manufacturing. This view~conflicts with sociological arguments, assuming highly differentiated processes of digitalisation. We review the literature and empirically test the core assumption that digital technologies relate to organisational characteristics~and that adoption differs according to the type of technology. We analyse German IAB-Establishment-Panel data, which contains organisation-level information, including digital technologies. Our results show a lead of manufacturing in the adoption of digital production technologies. Regarding other digital technologies, manufacturing performs on par or is outperformed by specific service industries. Additionally, the usage of digital technologies relates to organisational characteristics, other than industry (e.g., establishment size, age, competition, employees' qualification). The relationship patterns largely persist across technologies, with some technology-specific variants. Our empirical results underline the embeddedness of digitalisation processes in Germany and underline the relevance of the technologies in question.
Keywords: 330; digital transformation; Industrie 4.0; organisational characteristics; social embeddedness; technology adoption; types of technology